HUBUNGAN POLA ASUH ORANG TUA DAN PENGGUNAAN MEDIA SOSIAL DENGAN PERILAKU BULLYING PADA REMAJA - Pramisti Dewi, Asya Nova (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Parenting styles and social media usage had a significant impact on adolescent behavior, including bullying behavior. The purpose of this study was to determine the relationship between parenting styles and the use of social media with bullying behavior in adolescents. Correlational quantitative research design with a cross—sectional approach. The sampling technique used was proportionate stratified random sampling, with a sample size of 279 respondents. The independent variables in this study were parenting styles and the use of social media, while the dependent variable was bullying behavior. The instruments used for the parenting style questionnaire used the Parenting Style and Dimension Questionnaire (PSDQ), the social media usage questionnaire used the Bergen Social Media Addiction Scale (BSMAS), and the bullying behavior questionnaire used the Adolescent Peer Relations Instrument (APRI). Data analysis used the Spearman Rho test. The results of the bivariate statistical test in the study of parenting styles with bullying behavior showed a p value = 0.000 where p (<0,05) and r = 0.454, so it could be concluded that there was a relationship between parenting styles and bullying behavior. The bivariate statistical test of social media usage with bullying behavior showed a p value = 0.000 where p (<0,05) and r = 0.427, so it could be concluded that there was a relationship between social media usage and bullying behavior. Parents are helping to build positive relationships with others, clear boundaries from parents, and well-monitored use of social media were a strong combination for adolescents to avoid bullying behavior.